(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Growth performance of Hypophthalmichthys molitrix (Silver carp) and Barbodes gonionotus (Sar puti) fingerlings were studied separately in aquaria by feeding cultured microalgae (Chlorella ellipsoidea, Scenedesmus obliquus and Spirulina platensis) in different combinations for a period of 21 days. Fertilizer factory effluent was used to grow these microalgae. Significantly (p<0.05) higher weight gain of H. molitrix (81.16%), was in the treatment T2 (Rearing by feeding 100% S. platensis) and the minimum percentage (- 4.29%) was obtained in the control (fed on fishmeal and mustered oil cake). Specific growth rate (SGR, %/day) of H. molitrix were determined - 0.21 to 2.84 for all the treatments which was significantly (p<0.05) higher in T2. Survival rate of H. molitrix was 25.90 to 77.80%. In the case of B. gonionotus, significantly (p<0.05) higher weight gain (149.10%) was observed in t2 (Rearing by feeding 100% S. platensis). The SGR (%/day) of B. gonionotus were ranged from 2.25 to 4.33 which was significantly (p<0.05) higher in t2 than all other treatment except control. Survival rate of B. gonionotus was ranged from 97.78% to 100%. The reared fingerlings were found nutritionally rich. Key words: Fingerlings; Microalgae; Growth performance; Specific growth rate. DOI: 10.3329/bjsir.v45i4.7328 Bangladesh J. Sci. Ind. Res. 45(4), 315-322, 2010